Effects of luteectomy in early pregnancy on the maintenance of gestation and plasma progesterone concentrations in the viviparous temperate lizard Barisia imbricata imbricata - Martínez-Torres, Martín (BioMed Central, 2010)
BACKGROUND: Several studies have shown that the corpus luteum is the principal source of progesterone during the gravidity period in reptiles; however, its participation in the maintenance of gestation in the viviparous squamata is in dispute. The effects of ovariectomy or luteectomy vary according to the species and the time at which the procedure is performed. In this paper, we describe the effects of luteectomy during early pregnancy on the maintenance of gestation and progesterone concentrations in the temperate Mexican viviparous lizard Barisia imbricata imbricata. METHODS: Twenty-four lizards were subjected to three different treatments: luteectomy, sham luteectomy or non-surgical treatment, and blood samples were obtained before and after surgical treatment at different stages of gestation to determine the effects of luteectomy on the maintenance of gestation and progesterone concentrations. RESULTS: Spontaneous abortion was not observed in any of the females. However, luteectomy provoked abnormal parturition and a significant reduction in the number of young born alive. Parturition was normal in untreated females as well as those submitted to sham luteectomy. The surgical treatment also caused a significant reduction in progesterone concentrations in luteectomised females during early and middle gestation. However, no significant differences in hormone concentrations were observed among the three groups during late gestation or immediately post-parturition. CONCLUSIONS: Our observations indicate that the presence of the corpus luteum is not necesary for the maintenance of gestation, but that it does participate in parturition control. Moreover, the corpus luteum of the viviparous lizard B. i. imbricata produces progesterone, at least during the first half of pregnancy, and that an extra-ovarian source of progesterone must maintain gestation in the absence of luteal tissue.